2002
DOI: 10.1124/dmd.30.8.911
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2E1 (CYP2E1) is Essential for Acrylonitrile Metabolism to Cyanide: Comparative Studies Using CYP2E1-Null and Wild-Type Mice

Abstract: ABSTRACT:Acrylonitrile (AN) is a rodent carcinogen and suspected human carcinogen. Metabolism of AN proceeds via conjugation with glutathione or epoxidation via cytochrome P4502E1 (CYP2E1) to cyanoethylene oxide (CEO). It was hypothesized that CEO metabolism via epoxide hydrolase (EH) is the primary pathway for cyanide formation. The objective of this work is to assess the enzymatic basis of metabolism to cyanide. Male wild-type and CYP2E1-null mice received 0, 2.5, 10, 20, or 40 mg of AN/kg by gavage, and cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…It was hypothesized that CEO metabolism via epoxide hydrolase is the primary pathway for cyanide formation [2]. Glutathione (GSH) conjugation has been shown to be depleted following ACN treatment in vivo and may decrease the antioxidant capacity of the cells resulting in an overall increase in intracellular reactive oxygen species (ROS) and oxidative damage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized that CEO metabolism via epoxide hydrolase is the primary pathway for cyanide formation [2]. Glutathione (GSH) conjugation has been shown to be depleted following ACN treatment in vivo and may decrease the antioxidant capacity of the cells resulting in an overall increase in intracellular reactive oxygen species (ROS) and oxidative damage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylonitrile (ACN) is a widely used monomer in the production of synthetic fibers, rubbers, plastics and as a chemical intermediate in the synthesis of a variety of products including antioxidants, pharmaceuticals, and dyes [1,2]. The important use of ACN in clinical practice is in the manufacture of high permeable dialysis tubings [3] and in the synthesis of artificial membrane to encapsulate Langerhans islets implants [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ensuing studies demonstrated that the CYP2E1 enzyme metabolizes a number of low molecular weight alkyl nitriles (Ghanayem et al, 1999) and is responsible for the initial metabolism of acrylonitrile leading to cyanide release (Wang et al, 2002;Chanas et al, 2003;El Hadri et al, 2005). However, the role of this or other metabolic routes in sensory effects remains poorly understood.…”
Section: Role Of Cyp2e1-mediated Metabolism In the Acute And Vestibulmentioning
confidence: 99%
“…Ethanol pretreatment induces CYP 2E1 activity (Daiker et al 2000), which has been shown to play a critical role in the bioconversion of AN, promoting degradation of AN and the release of cyanide ions (Sumner et al 1999;Wang et al 2002).…”
Section: Discussionmentioning
confidence: 99%